Comportamiento agronómico de cinco de cinco cultivares de fréjol arbustivo (Phaseolus vulgaris L.) - Tamayo Romero, Vicente Rogerio (2011)
The cultivation of beans (Phaseolus vulgaris L.) is the most important food legume in the world, constituting a major source of protein. The trial was conducted in the Santa Rosa de la Parroquia Puyo, Canton and Pastaza Province, at latitude 78 º 02 'West and 1 º 29' south, at an altitude of 965 meters, the duration was 100 days and had as main objective to assess the agronomic performance of five cultivars of bush beans. Treatments under study were: T1 = Cargabello; Canario Peruvian T2 = T3 = Calima, T4 = panamito, T5 = Capulí. We used a total of 675 bean plants, ie 135 plants per replicate and treatment. Design We used a randomized complete block (RCB) with five treatments and five replications. The variables studied were: Percentage of emergence, days to flowering, plant height at flowering, number and size of pods per plant, days to harvest green, green performance (tender pods / plant), number of pods per plant, green yield in kg per hectare, susceptibility to pests and diseases and the corresponding economic analysis. The variety Cargabello showed early flowering (32.36 days), greater plant height (61.24 cm), lower incidence of disease (2.75), greater number of pods (50.35), higher yield per plant (112.70 g) and per hectare (5284.53 kg). The variety Capulí was later to reach physiological maturity (75 days), and variety was the earliest Calima (56.75). The most cost effective benefit (0.14) was reported to the variety Cargabello.